The Effectiveness Of Multidisciplinary Infection Control Strategies In Improving Healthcare Quality And Patient Safety A Systematic Review (The Review of Diabetic Studies, 2025)
Background:Healthcare-associated infections (HAIs) remain a major global challenge, significantly affecting patient safety, healthcare quality, and health system sustainability. Despite advances in infection prevention and control (IPC), fragmented and discipline-specific approaches have shown limited effectiveness. Multidisciplinary infection control strategies, which integrate the coordinated efforts of healthcare professionals across multiple disciplines, have emerged as a comprehensive approach to addressing the complex nature of infection transmission in healthcare settings.Objective:This systematic review aimed to evaluate the effectiveness of multidisciplinary infection control strategies in improving healthcare quality and patient safety outcomes across diverse healthcare settings.Methods:A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Electronic databases including PubMed/MEDLINE, Scopus, Web of Science, CINAHL, and the Cochrane Library were searched. Studies assessing multidisciplinary infection control interventions and reporting outcomes related to healthcare quality or patient safety were included. Ten studies met the inclusion criteria. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool and Joanna Briggs Institute (JBI) critical appraisal tools, as appropriate. Due to heterogeneity in study designs and outcome measures, a narrative synthesis was performed.Results:The included studies demonstrated that multidisciplinary infection control strategies were consistently associated with improved adherence to infection prevention practices, enhanced healthcare quality indicators, and favorable trends in patient safety outcomes. Interventions combining education and training, audit and feedback mechanisms, standardized care bundles, surveillance systems, and leadership engagement showed the most consistent benefits. Several studies reported reductions in healthcare-associated infection rates, while others highlighted improvements in hand hygiene compliance, antimicrobial stewardship, and safety culture.Conclusion:Multidisciplinary infection control strategies are effective in enhancing healthcare quality and patient safety. Team-based, integrated approaches that align clinical practice with organizational support and continuous quality improvement appear to be particularly beneficial. Despite positive findings, variability in study designs and outcome measures limits direct comparison. Future research should focus on standardized metrics, long-term sustainability, and implementation across diverse healthcare contexts to strengthen the evidence base.